2017
DOI: 10.1093/gbe/evx138
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Oseltamivir and Favipiravir on Influenza A Virus Evolution

Abstract: Influenza virus inflicts a heavy death toll annually and resistance to existing antiviral drugs has generated interest in the development of agents with novel mechanisms of action. Favipiravir is an antiviral drug that acts by increasing the genome-wide mutation rate of influenza A virus (IAV). Potential synergistic benefits of combining oseltamivir and favipiravir have been demonstrated in animal models of influenza, but the population-level effects of combining the drugs are unknown. In order to elucidate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…0:25g in the case where the correct value of N is specified. These illustrative parameter values were chosen to match general features of common viral experimental evolution studies (e.g., Foll et al 2014a;Bank et al 2016;Ormond et al 2017).…”
Section: Estimation Of C With Mmc-abcmentioning
confidence: 99%
“…0:25g in the case where the correct value of N is specified. These illustrative parameter values were chosen to match general features of common viral experimental evolution studies (e.g., Foll et al 2014a;Bank et al 2016;Ormond et al 2017).…”
Section: Estimation Of C With Mmc-abcmentioning
confidence: 99%
“…The influenza virus RdRP consists of the viral proteins PB1, PB2, and PA. All three subunits contribute to the formation of the polymerase active site, which is strongly conserved and therefore a good target for antiviral drugs as the functional constraints on the amino acids of the active site may preclude the emergence of resistance ( 24 ). So far, experimental studies have not found any mutations in influenza viruses that lead to significant resistance against favipiravir ( 11 , 16 , 25 – 29 ). In addition, no resistant mutants have yet been identified in animal models ( 19 ) or in patients treated with favipiravir ( 30 ).…”
mentioning
confidence: 99%
“…Also working in IAV, Ormond et al (2017) examined the combined effect of favipiravir with oseltamivir, a widely-used treatment with well-studied resistance mutations. A similar mutational meltdown outcome was observed, with the selective sweeps of oseltamivir-resistant mutations appearing to actually speed population decline, owing to the resulting hitchhiking of linked deleterious variants in the viral population (and see the related work of PĂ©nnison et al 2017).…”
mentioning
confidence: 99%